Conservation of Cajamarquilla by Albert Giesecke, a comparative analysis with the restoration activities in Pachacamac, 1938 - Asencios Lindo, Rodolfo (2023)
Cajamarquilla, an important archaeological complex located east of Lima. It has an occupation from the Early Intermediate (200-600 AD) to the Late Intermediate (900-1440 AD). It has been the object of various archaeological investigations from the beginning of the 20th century to the present; however, despite numerous studies, the conservation carried out by Albert Giesecke in 1938, carried out in parallel in Pachacamac in the south west of Lima, is unknown. The present study seeks to describe the activities and level of intervention in Cajamarquilla with respect to Pachacamac through the review of unpublished information from the archive, publications, photographic record, the state of conservation and the activities carried out are explored, to subsequently analyze said activities comparatively. This concludes that, although there are similarities in Giesecke's actions, in the political, technical-methodological and management aspects, the conservation of Cajamarquilla was less complex due to its state of conservation, geographical location and historical knowledge; while Pachacamac, its coastal proximity, agents of marine deterioration and scientific studies allowed for greater conservation activities. This study opens the search for other archaeological interventions that allow us to understand the historical, theoretical, methodological and technical process of the conservation of pre-hispanic monuments in Peru.